Into the Night : Cabarets and Clubs in Modern Art - Ostende, Florence; Benzi, Fabio; Dennis Cate, Phillip; Cottrell, Jo; Floe, Hilary; Gigli, Elena; Johnson, Lotte; Kennedy, Thomas; Kirschke, Amy Helene; Klee, Alexander; Klich, Lynda; Meyer, Raimund; et al. (Londen : Prestel Publishing, 2019)
Auriol, George ; Balda, M. ; Lunel, Fernand ; Morin, Louis ; Neumont, Maurice ; Rivière, Henri ; Somm, Henry ; Fuller, Loïe ; Chéret, Jules ; de Toulouse-Lautrec, Henri ; Czeschka, Carl Otto ; Hoffmann, Josef ; von Divéky, Josef ; Burra, Edward ; Du Bois, W.E.B. ; Lawrence, Jacob ; Douglas, Aaron ; Dodo ; Höch, Hannah ; Cueto, German ; Fernandez, Justino ; Leal, Fernando ; Tesorero, Victor ; Cabrera, Rosario ; Depero, Fortunato ; Vela, Arqueles.
on the occasion of the exhibition Into the Night: Cabarets and Clubs in Modern Art, Londen, Barbican Centre, 4 October 2019 - 19January 2020 / Belvedere, Wenen, 14 February - 1 June 2020
boek